2012
DOI: 10.1007/s11033-012-2131-9
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and promoter analysis of squalene epoxidase gene from Withania somnifera (L.) Dunal

Abstract: Withania somnifera is a rich reservoir of pharmaceutically active steroidal lactones known as withanolides. The plant is well characterized in terms of its chemistry and pharmacology, but very little is known about the pathway involved in the biosynthesis of withanolides. The present investigation describes the cloning, characterization and expression of squalene epoxidase (SE) gene from W. somnifera. SE (SQE; EC. 1.14.99.7) is one of the rate limiting enzymes in the biosynthesis of triterpenoids, catalyzing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…Restriction of secondary metabolite biosynthesis to particular tissue(s) in plants is mostly executed by regulating the expression levels of biosynthetic pathway genes. In accordance with this fact, our previous studies have shown elevated expression profile of three upstream genes, namely squalene synthase (WsSQS), squalene epoxidase (WsSQE), and cytochrome P450 reductase 2 (WsCPR2) of withanolide biosynthetic pathway in leaves as compared with other tissues (8,17,50). Additionally, enhanced expression of obtusifoliol-14-demthylase (CYP51) and sterol methyl transferase (SMT-1), which constitute an important part of downstream withanolide biosynthetic pathway, has also been reported in leaves of Ws (51).…”
Section: Discussionsupporting
confidence: 65%
“…Restriction of secondary metabolite biosynthesis to particular tissue(s) in plants is mostly executed by regulating the expression levels of biosynthetic pathway genes. In accordance with this fact, our previous studies have shown elevated expression profile of three upstream genes, namely squalene synthase (WsSQS), squalene epoxidase (WsSQE), and cytochrome P450 reductase 2 (WsCPR2) of withanolide biosynthetic pathway in leaves as compared with other tissues (8,17,50). Additionally, enhanced expression of obtusifoliol-14-demthylase (CYP51) and sterol methyl transferase (SMT-1), which constitute an important part of downstream withanolide biosynthetic pathway, has also been reported in leaves of Ws (51).…”
Section: Discussionsupporting
confidence: 65%
“…This expression pattern of OSC/CS is in correlation with the higher amounts of withanolides in the leaves (Dhar et al, 2014). As discussed above, expression of upstream genes like SQS, SQE, and cytochrome P450 reductase 2 (CPR2) was also found to be higher in leaves as compared to other tissues Rana et al, 2013;Razdan et al, 2013). Additionally, enhanced expression of obtusifoliol-14-demthylase (CYP51) and sterol methyl transferase (SMT-1) that constitute important part of downstream withanolide biosynthetic pathway has also been reported in leaves (Pal et al, 2011).…”
Section: Identification and Characterization Of Pathway Genesmentioning
confidence: 52%
“…Besides Panax species and yeast, SE was also characterized in Euphorbia tirucalli (Uchida et al 2007), Withania somnifera (Razdan et al 2013), Arabidopsis (Laranjeira et al 2015), Gynostemma pentaphyllum (Guo et al 2016) etc.…”
Section: Enzymes Of Methylerythritol 4-phosphate (Mep) Pathwaymentioning
confidence: 99%